Complete chloroplast genome sequence and phylogenetic analysis of Torenia fournieri. Issue 7 (3rd July 2021) - Chen, Gang; Wang, Li-guo; Wang, Ying-hua
Abstract: Torenia fournieri belongs to the genus Torenia in the family Linderniaceae. The complete chloroplast genome of T. fournieri was sequenced and analyzed by Illumina sequencing in this study. The full length of the complete chloroplast genome is 153, 938 bp, containing a pair of inverted repeat regions of 24, 805 bp (IRa and IRb) separated by a large single copy region (LSC) of 85, 498 bp and a small single copy region (SSC) of 18, 830 bp. The T. fournieri chloroplast genome encodes 131 genes, comprising 87 protein-coding genes, 36 tRNA genes, 8 rRNA genes, without pseudogene. Phylogenetic analysis showed that T. fournieri was closely related to T. benthamiana and T. concolor within the genus Torenia in family Linderniaceae.